Leisure Parks in the Regional Centers of the Samarkand Region - Islamova Dilnoza Gayratovna; Abdalimova Zilola (Zien Journals, 2022)
The article discusses the functional areas of district parks, social and cultural events, attractions, sports grounds, children's areas, landscape solutions for quiet areas and their standards.
Keywords: Landscape arrangements; park; landscape syst